On some total social places: an enditorial... - Andrea Mubi Brighenti (lo Squaderno, 2010)

(untitled)
Let us consider a few different types of socio-spatial formations: utopia, dystopia and heterotopia. Heterotopia has been famously described as a ‘really existing’ or ‘effectuated’ utopia, which in turn has been succinctly yet effectively characterized as ‘the best of all impossible worlds’. Taking the element of judgment or evaluation into consideration, utopia has its double (its Doppelgänger, to be sure) known as dystopia, which is utopia itself seen from a ‘slightly different’ perspective – the slight difference that separates dreams from nightmares. In other words, whether we are in a ‘eu-’ or ‘dys-’ world depends on our evaluation of the degree of emancipation and oppression that has been created.